The Role of transformal leadership in local governments’ efficiency - Matkó, Andrea (Acta Agraria Debreceniensis, 2013)
Local governments had to respond to the challenges of the dynamically changing environment. A key element of the rapid adaptation lies in the right leadership. The local governments also recognized that the traditional management principles are found not to be effective in today’s economic, political and social challenges. The employees of the organizations are successful in the attainment of leadership, which are planning the next year, performance-based, as well as the leading is diplomatic, charismatic-development, group integrators. The investigated local governments’ middle level leaders believe that in the current economic and political situation only those organizations able to keep up, which emphasize the trans-formal leadership.